PENGARUH KECERDASAN EMOSIONAL DAN MODAL SOSIAL TERHADAP KEMANDIRIAN BELAJAR SISWA DALAM PEMBELAJARAN IPS - Lili Dianah (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2017)
The study aims to measure and analyze the influence of emotional intelligence and social capital towards self-regulated learning. This study used a quantitative approach and survey method. The samples are 400 students from 16 Junior High Schools grade 8th in West Bandung regency. The research used stratified random sampling. The results showed that emotional intelligence and social capital positive and significant impact on student’ self regulated learning. The influence of emotional intelligence was 0,447, or 20% toward self regulated learning, while the remaining (80%) was influenced by other factors. The influence of social capital was 0.232 or 5.4%, toward self regulated learning, while the remaining (94.6%) was influenced by other factors. Simultaneously, the emotional intelligence and social capital influenced 33.2% toward self regulated learning and the remaining (66.8%) was influenced by other factors. In this study the variables of emotional intelligence has the most impact on self regulated learning. The implication showed that the student’s self regulated learning could be enhanced by increasing the students’ emotional intelligence and social capital.